ANALISA PENOMORAN DI PUSKESMAS SUGIHMUKTI GUNA MENCEGAH TERTUKARNYA BERKAS REKAM MEDIS - Andri Ramadhan; Dilla Rizkyani Fratama; Syaikhul Wahab (Jurnal Inovasi Penelitian, 2021)
The implementation of medical record numbering at the Sugihmukti Health Center applies a Family Numbering System, where documents in one family will be stored in one folder and given an identity with a family number. This Family Numbering System provides convenience in retrieval of Medical Records, saves storage space, and prevents medical record files from being exchanged. The medical record storage shelves at the Sugihmukti Health Center are grouped based on the area where the patient lives, making it easier for officers to find the file. The purpose of this study was to determine the cause of medical record files being confused, to identify the medical record numbering system at the Sugihmukti Health Center. This research method uses qualitative methods and descriptive cases. The population is 40,020 medical record files and the sample is 4,002 medical record files as respondents. The numbering classification used is the first 2 digits, namely the area code, the middle 4-6 digits as the number of the head of the family, and the last 2 digits as the family sequence code. The data collection technique we used in this study was observation. The results of the study were one medical record number was used for all family members classified by area code and family order code. From the results of the study, it was found that the number of medical records that were duplicated was (2.99%) and the number of medical records that were not duplicated was (97.11%). Based on the results of our research, it can be concluded that the limitations of Human Resources cause performance to be less than optimal.